توظيف الإنفوجرافيك في معالجة القضايا الصحية في الدول العربية عبر موقع التواصل الاجتماعي "تويتر" دراسة حالة على موضوع فيروس كورونا "Covid-19" المستجد - زناتي، ريم نجيب Zanati, Reem Najib (جامعة الأزهر - كلية الإعلام بالقاهرة, 2020)
تبحث الدراسة في دور الإنفوجرافيك المقدم في الحسابات الرسمية لوزارة الصحة في الدول العربية عبر موقع التواصل الاجتماعي (تويتر) في معالجة القضايا الصحية، بالتطبيق على موضوع فيروس (كورونا COVID-19) المستجد، ونشر التوعية الصحية بين أفراد المجتمعات العربية، وذلك في الفترة الزمنية (من 1 مارس إلى 31 مايو 2020)، وتوصلت النتائج إلى أن الصفحة السعودية تفوقت في حجم الاهتمام بالإنفوجرافيك الذي يعالج القضايا الصحية بنسبة بلغت (44.7%)، يليها الصفحة الكويتية بنسبة (30.5%)، ثم المصرية بنسبة (24.7%)، وبالنظر لوظيفة الإنفوجرافيك المستخدم في معالجة موضوع فيروس كورونا covid- 19 في المواقع الثلاث مجتمعة، نجد أن "التوعية" تصدرت المرتبة الأولى بنسبة (36.9%)، واتبعت مواقع الدراسة، في أساليب عرض المعلومات بالإنفوجرافيك الأسلوب الخبري في المقام الأول بنسبة (45.8%)، وجاء في الترتيب الثاني "الأسلوب التوعوي" بنسبة (36.5%)، وتصدرت "نسب وأعداد مرضى فيروس كورونا COVID- 19"، مضمون الإنفوجرافيك بنسبة (38.5%)، ثم في الترتيب الثاني "الإرشادات الوقائية من فيروس كورونا "COVID- 19".
The study examines the role of the infographic presented in the official accounts of the Ministry of Health in the Arab countries via the social networking site (Twitter) in addressing health issues by applying to the topic of the emerging Corona virus (COVID 19), and spreading health awareness among members of Arab societies, during the period of time (From March 1 to May 31, 2020), and the results are as follows: - The Saudi page outperformed in terms of interest in infographics that dealt with health issues by (44,7%), followed by the Kuwaiti page (30,5%), then the Egyptian page (24,7%). - In view of the function of the infographic used to address the topic of the covid-19 virus in the three sites combined, "awareness" topped the first place with a rate of (36.9%). - The study sites followed the methods of presenting information through the infographic in the first place with the news method with a rate of (45.8%), and the "awareness style" came in second place with a rate of (36.5%), - The content of the infographic "The ratios and numbers of patients with the Coronavirus COVID-19, at a rate of (38.5%), is issued, followed in second order by the "preventive instructions from the Coronavirus" COVID-19.
Keywords: الإدارة الصحية -- فيروس كورونا "كوفيد-19" -- مواقع التواصل الاجتماعي -- الوطن العربي